Effects of dietary protein combined with high-intensity exercise in restoring skin health in male rats - Gunadi, Julia Windi; Lesmana, Ronny; Kastella, Faysal; Tarawan, Vita Murniati; Goenawan, Hanna; Gunawan, Decky; Jasaputra, Diana Krisanti (Faculty of Medicine, Universitas Trisakti, 2025)
Background Protein is essential for skin integrity, while exercise modulates cellular and molecular processes that regulate autophagy, mitochondrial biogenesis, and collagen synthesis. This study evaluates the combined effects of dietary protein restriction and varying exercise intensities on epidermal thickness, autophagy markers (LC3, p62), mitochondrial biogenesis (PGC1α), and collagen synthesis (Col1a1, Col3a1) in male Wistar rats. Methods An experimental laboratory study was conducted involving 32 male Wistar rats. They were randomized into 8 groups: control, low protein, low intensity, group IV, moderate intensity, moderate intensity low protein, high intensity, and high intensity low protein. Low protein diet (5%) compared to the control (24%) was given for 60 days, while the exercise regimen was eight weeks of treadmill exercise (low/10 m per minute, moderate/20 m per minute, and high intensity/30 m per minute) for 30 minutes a day, five days a week. Epidermal thickness, LC3, p62, PGC1α, Col1a1, and Col3a1 mRNA expression were measured at the end of the study. One-way ANOVA/Kruskal-Wallis followed by Tukey HSD/Mann–Whitney test was used to analyze the data. Results A low-protein diet significantly reduced epidermal thickness (p=0.048), increased LC3 (p=0.043) and p62 (p=0.011), indicating impaired skin regeneration and autophagy. However, exercise, especially at high intensities with low protein, mitigated this effect by increasing both LC3 (p=0.011) and PGC1α (p=0.011). Conclusions These findings highlight the compensatory role of exercise in maintaining tissue integrity under protein-deprived conditions in male rats. High-intensity exercise potentially enhances autophagy and mitochondrial biogenesis.